Development of a Scale to Assess Socioemotional Skills in Argentine Children Aged 9 to 12 Years - Zamora, Eliana Vanesa (2024)
Socioemotional skills allow us to understand and manage emotions, to set and reach positive goals, to maintain positive relationships, and to make responsible decisions. This study aimed to develop and validate a scale to assess these skills in 9-to-12 years old Argentinian children. 263 fourth, fifth and sixth graders (age M=10 years, 4 months) from Mar del Plata, Argentina answered to the developed items, along with the scales CERQ-k and DERS. The final version contained 26 items, grouped, according to factorial analyses, in four dimensions in line with the background theory (social skills, emotional regulation, growth mindset and self-control). The scale showed adequate internal consistency (α=.87), test-retest stability (r = .67), evidence of content validity according to expert judgments, and of criterion validity through associations with adaptative strategies and difficulties in emotional regulation. This scale allows for easy and reliable assessment of socioemotional skills, in research, clinical and educational contexts.